Currents' physical components (CPC): Case studies in single phase systems - Marcelo, Alexandre Borges [UNESP]; De Andrade Alves Santos, Risomar [UNESP]; Tirolli, Marcelo Nogueira [UNESP]; Santos, Lucas Arna Matos Dos [UNESP]; Marafao, Fernando Pinhabel [UNESP]; Goncalves, Flavio Alessandro Serrao [UNESP]; Paredes, Helmo Kelis Morales [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
This paper intends to apply in selected cases the Currents' Physical Components (CPC) Theory, developed by Czarnecki to interpret power properties through the decomposition of the system's currents into orthogonal components and relating them to a physical interpretation. In order to analyze its applicability in single-phase systems with either non-sinusoidal sources and/or non-linear loads, as well as to deepen the understanding of the CPC algorithm, several cases were simulated and analyzed with the PSIM software. From a theoretical point of view, most simulated cases behave as expected, where the components agree with the interpretation of the theory.
Keywords: Currents' Physical Components; Non-sinusoidal Source; Power Theories; Non-sinusoidal; Nonlinear load; Orthogonal components; Physical components; Physical interpretation; Power theory; Single phase system; Theoretical points